University Teacher's Evaluation in Spain - Francisco Javier Tejedor Tejedor; Jesús Miguel Jornet Meliá (Universidad Autónoma de Baja California, 2008)
This article intends to make a brief overview about the performance evaluation for university teachers in democratic Spain. It contents: a) considerations about teaching evaluation, in order to delimit the authors' position in this matter, due to the fact that this position obviously conditions any revision; b) a brief summary of the history of university teachers evaluation in Spain during the last years, since the Spanish Constitution of 1978 approval; c) a typology of the evaluation plans, in order to define a map of the planning lines for evaluations applied in Spain; d) the technical guidelines for teachers´ evaluation and presentation of the current model, exampled by its application in the university of Salamanca; and e) as a conclusion, some considerations about the consequences of evaluation and its entailment with the professionalization of university teachers.